Data Science and Analytics for SMEs Consulting, Tools, Practical Use Cases - Tolulope, Afolabi Ibukun (Berkeley, CA : Apress : Imprint: Apress, 2022)
Master the tricks and techniques of business analytics consulting, specifically applicable to small-to-medium businesses (SMEs). Written to help you hone your business analytics skills, this book applies data science techniques to help solve problems and improve upon many aspects of a business' operations. SMEs are looking for ways to use data science and analytics, and this need is becoming increasingly pressing with the ongoing digital revolution. The topics covered in the books will help to provide the knowledge leverage needed for implementing data science in small business. The demand of small business for data analytics are in conjunction with the growing number of freelance data science consulting opportunities; hence this book will provide insight on how to navigate this new terrain. This book uses a do-it-yourself approach to analytics and introduces tools that are easily available online and are non-programming based. Data science will allow SMEs to understand their customer loyalty, market segmentation, sales and revenue increase etc. more clearly. Data Science and Analytics for SMEs is particularly focused on small businesses and explores the analytics and data that can help them succeed further in their business. You will: Create and measure the success of their analytics project Start your business analytics consulting career Use solutions taught in the book in practical uses cases and problems .
Chapter 1: Introduction -- Chapter 2: Data for Analytics in Small Businesses -- Chapter 3: Business Analytics Consulting -- Chapter 4: Business Analytics Consulting Phases -- Chapter 5: Descriptive Analytics Tools -- Chapter 6: Predicting Numeric Outcomes -- Chapter 7: Classification Techniques -- Chapter 8: Advanced Descriptive Analytics -- Chapter 9: Case Study Part 1 -- Chapter 10: Case Study Part 2.
Keywords: Big data; Quantitative research; Data mining; Small business; Entrepreneurship; New business enterprises; Information technology-Management.; Big Data; Data Analysis and Big Data; Data Mining and Knowledge Discovery; Small Business; Entrepreneurship; Business Process Management